Debakarn Koorliny Wangkiny: steady walking and talking using first nations-led participatory action research methodologies to build relationships. Issue 1 (2nd January 2023) - Wright, Michael; Culbong, Tiana; Webb, Michelle; Sibosado, Amanda; Jones, Tanya; Guima Chinen, Tilsa; O'Connell, Margaret
ABSTRACT: Aboriginal participatory action research (APAR) has an ethical focus that corrects the imbalances of colonisation through participation and shared decision-making to position people, place, and intention at the centre of research. APAR supports researchers to respond to the community's local rhythms and culture. APAR supports researchers to respond to the community's local rhythms and culture. First Nations scholars and their allies do this in a way that decolonises mainstream approaches in research to disrupt its cherished ideals and endeavours. How these knowledges are co-created and translated is also critically scrutinised. We are a team of intercultural researchers working with community and mainstream health service providers to improve service access, responsiveness, and Aboriginal client outcomes. Our article begins with an overview of the APAR literature and pays homage to the decolonising scholarship that champions Aboriginal ways of knowing, being, and doing. We present a research program where Aboriginal Elders, as cultural guides, hold the research through storying and cultural experiences that have deepened relationships between services and the local Aboriginal community. We conclude with implications of a community-led engagement framework underpinned by a relational methodology that reflects the nuances of knowledge translation through a co-creation of new knowledge and knowledge exchange.